FACTORS INFLUENCING UTILISATION OF POSTNATAL CARE SERVICES AMONG MOTHERS AT KAJJANSI HEALTH CENTER IV, WAKISO DISTRICT NABAKOOZA TABITHA DIPLOMA IN NURSING. A CROSS-SECTIONAL STUDY. - Tabitha Nabakooza; Hasifa Nasereko (Student's Journal of Health Research, 2023)
Background: Mothers are so much vulnerable to complications after child delivery which can greatly affect their health to the extent of claiming their lives these complications are preventable if the mothers utilize the PNC services put in place. This study aimed to find out the factors influencing the utilization of postnatal care services among mothers at Kajjansi health center IV, Wakiso district. Methodology: A descriptive quantitative cross‑sectional study was conducted at Kajjansi health center IV, Wakiso district. A questionnaire was administered after obtaining informed consent from 36 respondents that were present at the time of data collection. These were selected using a simple random sampling method. Results were tabulated, analyzed using Microsoft Excel, and presented using frequency tables, pie charts, and graphs. Results: This study established that the majority of 32(88.9%) of the respondents were aged between 20 - 30 years, and nearly all, 33(91.7%) lived in towns. 23(63.9%) of the respondents had information about post-natal services and 21(58.3%) of them, their society encouraged them to seek medical care after giving birth at the health facility; 28(77.7%) said that their cultures did not encourage mothers to deliver without help from a health care provider whereas nearly two thirds 23(63.9%) of them said nurses and midwives treat the mothers in a good way as they go to seek for postnatal care services Conclusion: Mothers used PNC services and the factors below; women's residence, awareness of post-natal services, wealth status, marital status, occupation, antenatal care attendance, place of delivery, perceived accessibility of health facilities, and access to mass media messages, and many others were associated with greater use of PNC service. Recommendations: Educational programs with special emphasis on post-natal care services and mandatory participation in educational programs for all stakeholders are highly recommended to enhance the utilization of post-natal care services.